Molecular Phylogeny and Taxonomy of the Butterfly Subtribe Scolitantidina with Special Focus on the Genera Pseudophilotes, Glaucopsyche and Iolana (Lepidoptera, Lycaenidae) - Vladimir A. Lukhtanov; Anastasia V. Gagarina (Insects, 2022)
The Palearctic blue butterfly genus Pseudophilotes Beuret, 1958 is not homogenous regarding the morphology of its genital structures. For this reason, some of its species have been considered to be representatives of other genera of the subtribe Scolitantidina (subfamily Polyommatinae). Here, we address these taxonomic problems by analyzing the phylogenetic relationships between the genera, subgenera, and species of this subtribe inferred via the analysis of five nuclear and two mitochondrial DNA sequences. We demonstrate that the enigmatic Asian species P. panope (Eversmann, 1851) belongs to the genus Pseudophilotes but not to Praephilotes Forster, 1938 or Palaeophilotes Forster, 1938 and does not represent the independent genus Inderskia Korshunov, 2000, as hypothesized previously. We synonymize P. svetlana Yakovlev, 2003 (syn. nov.) and P. marina Zhdanko, 2004 (syn. nov.) with P. panope. We demonstrate a deep genetic divergence between lineages that were previously considered as subspecies of the single species Iolana iolas (Ochsenheimer, 1816). As a result, we confirm the multispecies concept of the genus Iolana Bethune-Baker, 1914. We show that the Holarctic genus Glaucopsyche can be divided into four subgenera: Glaucopsyche Scudder, 1872 (=Shijimiaeoides Beuret, 1958), Apelles Hemming, 1931, Bajluana Korshunov and Ivonin, 1990, and Phaedrotes Scudder, 1876.